Analisis Efektivitas Kamus sebagai Produk Kemas Ulang Informasi di Perpustakaan Universitas Perintis Indonesia - Mutia Salsabila; Cahyanti Cahyanti; Siti Mutia Yusroh (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
This study aims to analyze the effectiveness of dictionaries as repackaged information products at the Library of Universitas Perintis Indonesia. The research employed a qualitative approach using observation and interviews with librarians. The findings reveal that although both physical and digital dictionaries are available and in good condition, their utilization remains low. Dictionaries are only used when required for practical courses and are rarely accessed otherwise. Factors contributing to the low usage include limited promotion, insufficient information literacy, and the lack of integration between the dictionary collection and the academic curriculum. This situation results in the suboptimal contribution of dictionaries to students’ learning processes and information literacy. The study recommends strategies to increase dictionary utilization through active promotion, curriculum integration, information literacy training, and continuous evaluation. These findings are expected to serve as a reference for the development of academic library services, particularly in optimizing repackaged information products to support the learning needs of health science students.